The effect of WC-17Co thermal spray coating by HVOF and hard chromium electroplating on the fatigue life and abrasive wear resistance of AISI 4340 high strength steel - Souza, R. C.; Nascimento, M. P.; Voorwald, HJC; Pigatin, W. L. (Freund Publishing House Ltd, 2003)
One of the most interesting alternatives for replacement of hard chrome plating is tungsten carbide thermal spray coating applied by the high velocity oxy-fuel (HVOF) process which presents a safer, cleaner and less expensive alternative to chromium plating. The objective of this research is to compare the influence of the tungsten carbide-17cobalt (WC- 17Co) coating applied by high velocity oxy fuel (HVOF) process with that of hard-chromium electroplating on the fatigue strength and abrasive wear of AISI 4340 steel.
Keywords: WC-17Co thermal spray coating; hard chromium electroplating; abrasive wear; fatigue; HVOF